1990
DOI: 10.1091/mbc.1.9.649
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of endothelin mRNA and secretion in rat vascular smooth muscle cells: a novel autocrine function.

Abstract: Endothelin (ET), a peptide originally isolated from the supernatants of cultured endothelial cells, exerts a wide variety of biological effects in different tissues. Endothelial-cell-synthesized ET-1 has been proposed to act in a paracrine manner on adjacent smooth muscle cells (SMC) in vivo, with effects that include both vascular reactivity (vasodilation/vasoconstriction) and mitogenesis. This study, by the use of immunocytochemically characterized SMC (rVSMC) isolated from the aortas of spontaneously hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(120 citation statements)
references
References 56 publications
(65 reference statements)
4
114
0
2
Order By: Relevance
“…3 Thus, it is conceivable that a certain proportion of the increased vascular content of ET-1 originates in smooth muscle cells. However, no significant ir-ET-1 staining was found in the media of blood vessels from DOCA-salt hypertensive or uninephrectomized rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thus, it is conceivable that a certain proportion of the increased vascular content of ET-1 originates in smooth muscle cells. However, no significant ir-ET-1 staining was found in the media of blood vessels from DOCA-salt hypertensive or uninephrectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is a 21-amino acid peptide produced primarily in endothelial cells' but also in vascular smooth muscle cells. 3 Locally produced ET-1 exerts its effects in an autocrine and paracrine fashion to constrict blood vessels by acting on smooth muscle. Through its effect on endothelial cells, it induces the production of endothelium-derived relaxing factor and prostacyclin, which relax underlying smooth muscle cells.…”
Section: Increased Endothelin-1 Content In Blood Vessels Of Deoxycortmentioning
confidence: 99%
“…28 Purified, RNA containing lysates were slot-blotted directly onto Hybond N membrane (Amersham, UK), air-dried, and irradiated with ultraviolet light for 3 minutes at 302 nm to cross-link the RNA to the membrane. Hybridization of membranes to random-primed, radioactive probes (endothelin, 27 major histocompatibility complex [MHC] 29 occurred overnight at 65°C. 27 The endothelin specific probe used was a 1.1 kb, partial cDNA probe, cloned in the £coRI sites of the vector pUC 18.…”
Section: Northern Blotting and Densitometrymentioning
confidence: 99%
“…Hybridization of membranes to random-primed, radioactive probes (endothelin, 27 major histocompatibility complex [MHC] 29 occurred overnight at 65°C. 27 The endothelin specific probe used was a 1.1 kb, partial cDNA probe, cloned in the £coRI sites of the vector pUC 18. Using this enzyme, the insert was recovered and isolated.…”
Section: Northern Blotting and Densitometrymentioning
confidence: 99%
“…A previous study confirmed that ET-1 exerts its biological effect by autocrine and paracrine action, resulting in induction of self-expression. 22 Differences in animal models, species and tissue specificity may also play a role in these various findings.…”
Section: Discussionmentioning
confidence: 99%